(7.1*10^-7)*(8.6*10^-5)

= (7.1*8.6)*10^(-7+(-5))

= 61.06*10^-12

= (6.106*10^1)*10^-12

Each of the contributors to the product has 2 significant digits, so if you are concerned about that, you need to round the result to 2 significant digits. It would then be

6.1*10^-11

= (7.1*8.6)*10^(-7+(-5))

= 61.06*10^-12

= (6.106*10^1)*10^-12

**= 6.106*10^-11**Each of the contributors to the product has 2 significant digits, so if you are concerned about that, you need to round the result to 2 significant digits. It would then be

6.1*10^-11